The Role of Halal Certification of Food Products in Economic Improvement in the Batang Integrated Industrial Estate - Mustakim, Zaenal; Anggraeni, Dewi; Ali, Fachri; Kamal, Rahmat (Islamic Studies Journal for Social Transformation, 2023)
This study aims to analyze the role of halal certification on economic aspects by increasing the income of MSME actors in Kedawung village. The choice of location is in Kedawung village because it is directly adjacent to the Batang Integrated Industrial Estate. This research uses the Participatory method with a Participatory Rural Appraisal approach involving the active role of 25 MSME actors in Kedawung village, Batang Regency. The construct of this research was carried out in three stages, planning, implementing, and evaluating sustainable activities. Data collection techniques in this study were through observation, interviews, documentation studies, Focus Group Discussion (FGD), and literature studies. The results of this study show that; 1) Kedawung Village has the potential for people-based economic growth through MSMEs; 2) Halal certification can be a factor in increasing the income of MSME actors and providing trust to consumers who care about the halal aspects of food; 3) The Batang city government responded the existence of the Integrated Industrial Estate by creating an MSME Corner facilitated with halal certification and product digitalization. This research has implications for the benefits of halal certification for economic growth and sustainable development of halal tourism.